Penelitian Hadis: Ontologi, Epistemologi dan Aksiologi - Solihin Solihin (Prodi Ilmu Hadis Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2016)
Study of tradition (Sunnah) becomes very urgent to do, given is strategic position as one of the principal sources of Islamic teachings. Do not just study sanad but no less important to do well against matan. Because it’s central position is a study of hadith becomes important. This includes the study and understanding of the ins and out of the following hadith variety and its problems. Scientifically, the discourse requires format and accurate research methods to the study of this tradition.This article attempts to examine how the concept of tradition of research in ontology, epistemology and axiology, to then the study of hadith through research models type sanad and matan. The hope will give its own repertoire of how each researcher have the clarity of the concept in researching the traditions to be grounded.